Answer:
23
Step-by-step explanation:
Answer:
6.3
Step-by-step explanation:
1. 25 - 2n = n + 6
2. 25 = 3n + 6
3. 3n = 19
4. n = 6.3
9514 1404 393
Answer:
(x, y) = (-5, -6)
Step-by-step explanation:
The coefficients of y are the same, so we can eliminate y by subtracting one equation from the other. Here, we choose to subtract the first from the second, so that the coefficient of x ends up positive.
(-5x +5y) -(-6x +5y) = (-5) -(0)
x = -5 . . . . . . simplify
-6(-5) +5y = 0 . . . . . . substitute x into the first equation
6 +y = 0 . . . . . . . . . . divide by 5
y = -6 . . . . . . subtract 6
The solution to the system of equations is (x, y) = (-5, -6).
The sum of the angles equals 180
therefore
x+(1/4x)=180
1 1/4 x = 180
x=180/ 1 1/4
x=144
1/4 x =1/4(144)=36
2yards= 72 inches
72 inches= 6 feet
so now that you know that, you know that she needs 6 feet and already has 3 feet. so she just needs 3 feet more. but they are asking for the answer to be in inches.
3 feet= 36 inches
your answer in 36 inches